Donors define whether CD19+CD27+ tonsillar B cells are mostly memory or germinal-center B cells - Pérez, M. Eugenia (2015)
CD27 has been used by numerous indepen- dent groups as a pan-memory B-cell marker not only for the identiﬁcation of peripheral blood (PB) memory B cells (Bmem) but also for spleen Bmem, tonsillar Bmem and bone marrow Bmem. Through a Letter to the Editor , Kupperś group has criticized the experimental approach we used (that is, using only CD27 as a human-Bmem marker in tonsils) in the article in which we report a comparative analysis of human Bmem derived from PB and tonsils.5 We would like, in turn, to respond and address the issue.